Postoperative complications in total intravenous anesthesia with propofol compare with sevoflurane anesthesia: A retrospective study - Ozlem Kocaturk (Medicine Science, 2018)
The aim of us is to define the incidence of postoperative complications two anesthesia procedures. During the period between 01.01.2016 and 01.01.2017, totally 583 patients were included in the study, who had oral-maxillofacial surgeries. Anesthesia types were determined as propofol-based total intravenous anesthesia (TIVA) and sevoflurane-inhalation anesthesia (SA). Surgical types were divided into two groups, major and minor. Postoperative complications and recovery period were determined as tachycardia, bradycardia, hypertension, hypotension, recovery time, additional analgesia, nausea-vomiting. While TIVA was used 241 patients, SA was used 342 patients. Incidences of patients, having had major surgeries under TIVA, for additional analgesic, nausea-vomiting, and recovery period on average were found as 12.7%; 13.5%; 13min respectively. As for the patients having had minor surgeries under TIVA, the same values were 10.2%; 6.5%; 12min respectively. Incidences of patients, having had major surgeries under SA, for additional analgesic, nausea-vomiting, recovery period on average were found as 11.3%; 34.2%; 7min respectively. Patients having had minor surgeries under TIVA performed the same values as 9.8%; 19.5%; 5min respectively. It was observed that SA caused more nause-vomiting than TIVA; however, it had a shorter recovery period. We have been in the opinion of that SA absolutely must be done with nausea-vomiting premedication and that it could be preferred owing to the shorter recovery. [Med-Science 2018; 7(2.000): 290-4]